RELEVANSI NILAI-NILAI ASWAJA TERHADAP PENDIDIKAN CINTA TANAH AIR MENURUT KH. MARZUQI MUSTAMAR - Emi, Fahrudi; Diyah Ayu, Lestari; Khoiriyah, Khoiriyah (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2022)
Abstracs This research is a literature study research (Library research). The approach used is a qualitative approach by categorizing which is then interpreted in a descriptive-analytic manner. This means that the researcher examines the main ideas of KH. Marzuqi Mustamar about aswaja in the context of nationality as primary data. This study aims: 1. To describe the concept of aswaja according to the thinking of KH. Marzuqi Mustamar. 2. To explain the concept of patriotism education according to KH. Marzuqi Mustamar. 3. To explain the relevance of the concept of aswaja according to KH. Marzuqi Mustamar towards love for the homeland education. And secondary data sources as a support. From the results of the study, it can be explained that defending and loving the homeland is legally obligatory for all Indonesian people, especially Muslims regardless of the reformist movement that wants the Indonesian state to be changed to an Islamic state. From Aswaja's values ​​that are relevant to love of the homeland education according to KH. Marzuqi Mustamar is Tawasuth (balanced), I'tidal (perpendicular), Tasamuh (tolerance), Tawazun (balanced). Based on the findings of the researcher, it is hoped that all Indonesian people can understand and practice it for the creation of an Indonesian state that is baldatun toyyibatun warobbun ghofur.